Feeding and housing management practices of dairy animals in Rajnandgaon of Chhatisgarh plain - DEORAS, RAJIV; NEMA, R K; TIWARI, S P; SINGH, MOHAN (The Indian Journal of Animal Sciences, 2014)
Data were collected from 300 farmers from rural area covering 20 villages of all 9 blocks and 100 farmers from Rajnandgaon city to study. The information was collected from respondents on feeding and housing management practices of dairy animals by a questionnaire prepared. In urban area significantly (P